KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 PADANG PANJANG - Naluri, Kekeh; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is to describe reading comprehension skills, exposition text writing skills, and correlation reading comprehension skills and exposition text writing skills of class X students of Padang Panjang High School. The results of this study are three, namely (1) reading comprehension skills of students of class X exposition in SMA Negeri 1 Padang Panjang are in good qualifications, with an average value (80.68), (2) writing skills of students exposition writing class X SMA Negeri 1 Padang Panjang is in good qualifications  with an average grade (82.52), (3) there is a relationship between reading ability and writing exposition text skills in class X students of SMA Negeri 1 Padang Panjang, with degrees freedom n-1 at a 95% confidence level. T value (14.79) is greater than t table (0.168), that is tcount> t table (14.79> 1.68) so H0 is rejected and H1 is accepted because the test results prove that t count is greater than t table. Based on the results of the study, it was concluded that the reading comprehension skills of the exposition text correlated with the writing skills of the exposition text. The better the reading comprehension skills of exposition text, the better the writing skills of exposition text. Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Eksposisi